The Minimum Purchase Price policy in China and wheat production efficiency: a historical review, mechanisms of action, and policy implications - Chen, Yangyang; Cheng, Ming (Frontiers in Nutrition, 2025)
This study addresses challenges in China’s staple grain production efficiency by examining the impact of the Minimum Purchase Price policy (MPP) on wheat production efficiency from the perspective of price support. First, relevant literature on price intervention policies is collected, summarized, and organized. This paper reviews previous research findings on the effects of the Minimum Purchase Price policy, social welfare implications, pricing studies, and comparative analyses of wheat production efficiency. Second, the study outlines the development of the Minimum Purchase Price policy and wheat production efficiency, and theoretically analyzes the mechanism by which the policy influences production efficiency. Finally, four recommendations for enhancing grain policy and improving wheat production efficiency in China are proposed: a focus on balanced macroeconomic development and coordinated efficiency, accelerating the allocation of production factors to unlock wheat production’s potential, fostering a conducive external social environment for industrial integration, and optimizing the Minimum Purchase Price policy to maximize its benefits.